Diseño e Implementación de un Sistema Automatizado para Producción de Plántulas de Siembra en el Cantón Loja - Idrovo Contento, Hugo Adrían (2020)
The present thesis project is oriented at the realization of a prototype automated robotic system that will be responsible for the sowing and developing seedlings on a plot of 1 m2, as well as, the take of data through different sensors that will allow us measure different physical variables such as environmental temperature and humidity or the humidity of the earth, which can influence the growth of the seedling, all the information will be stored in a datalogger, where the user will count with the design of an easily accessible web interface and handling that will help it in the system management remotely. The project begins with the search for the state of the art of the parameters that a plant needs to grow optimally, as well as the different software and hardware used; the software and hardware used in the thesis project are of free diffusion (Open Source) that come in a variety of equipment and programs. This implementation can be made scalable, depending of economic resources and financing, the project is characterized to investigate in small plots for sowing and germination of seedlings, until larger spaces such as greenhouses where the commercialization would be large-scale. In the end, the automated system will facilitate the task of seedling generation sinse the system will be in charge of sowing, to water and monitoring the germination variables of the seedling, offering the user save time, better control of water and soil use, to large-scales, savings in hiring personnel for cultivation and in the long run a return on capital invested in the system.